From gender analysis to transforming gender norms: Using empowerment pathways to enhance gender equity and food security in Tanzania - Galiè, Alessandra; Kantor, Paula (Routledge, 2016)
Drawing on studies from Africa, Asia and South America, this book provides empirical evidence and conceptual explorations of the gendered dimensions of food security. It investigates how food security and gender inequity are conceptualized within interventions, assesses the impacts and outcomes of gender-responsive programs on food security and gender equity and addresses diverse approaches to gender research and practice that range from descriptive and analytical to strategic and transformative. The chapters draw on diverse theoretical perspectives, including transformative learning, feminist theory, deliberative democracy and technology adoption. As a result, they add important conceptual and empirical material to a growing literature on the challenges of gender equity in agricultural production.